Gambaran Peran Masyarakat dan Dinas Lingkungan Hidup dalam Pengelolaan Sampah di Kelurahan Mautapaga, Kecamatan Ende Timur, Kabupaten Ende Tahun 2023 - Waldetrudis A.L. Nggumbe; Agus Setyobudi; Soni Doke (Yayasan Literasi Sains Indonesia, 2024)
Every activity carried out by humans has the potential to produce waste. Garbage is something that really disturbs people's comfort and public health (Harun, 2017). Waste management is one way to deal with waste (Ricky, 2015). This research aims to describe the role of the community and the Environmental Service in waste management in Mautapaga Village, East Ende District, Ende Regency. This research is qualitative research using a descriptive approach. The informants in this research were 15 people, consisting of 11 families in Mautapaga Village, 3 Environmental Service staff, 1 Mautapaga Village staff and the technique for determining informants was carried out purposively. The results of the research show that the role of the community and the environmental service has not been implemented properly, there are many people who still have deviant behavior in waste management and the Environmental Service has not provided facilities and infrastructure evenly. Waste management has not been implemented because there are no separate waste bins in the Mautapaga sub-district for organic and inorganic waste. Suggestion: the government and community are expected to be able to play an active role in providing and seeking information related to waste management. The community is expected to be able to have their own trash can in each household to avoid littering, and DLH is expected to be able to provide outreach and education regarding waste management.